Pengembangan Strategi Bisnis Berbasis Financial Untuk Meningkatkan Kompetensi Pengelolaan Keuangan Pelaku UMKM - Gustia Harini; Nora Susanti; Indra Mulia Pratama; Dina Amaluis; Erita (CV Abid Abadi Jaya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting economic growth; however, many still face challenges in financial management and business strategy development. This community service program aimed to enhance the knowledge and skills of MSME owners in developing financial-based business strategies through effective financial management. The program employed the Participatory Learning and Action (PLA) approach, consisting of observation, needs assessment, training, interactive discussions, practical sessions, mentoring, and evaluation. The participants were MSME owners who had limited capabilities in financial record-keeping and in utilizing financial information for business decision-making. The results indicated an improvement in participants' understanding of transaction recording, preparation of simple financial statements, cash flow management, and financial analysis as the basis for business strategy formulation. Furthermore, participants were able to develop business strategies based on financial information, enabling more effective and informed decision-making. The program positively contributed to improving financial literacy and managerial capacity among MSME owners, thereby supporting business sustainability. Continuous mentoring is recommended to ensure the consistent implementation of financial-based business strategies and to achieve long-term benefits.